Sarcopenia in the elderly with a history of copd/asthma : results of the SABE-Bogotá study (2017)
Introduction It has been reported that sarcopenia frequently co-exists with COPD/asthma, and can significantly affect quality of life and the control of chronic diseases. The aim of this study is to describe the association between COPD/asthma and sarcope